14. Coagulation disorders in children with acute pancreatitis at the Vietnam National Children's hospital - Thuong, Nguyen Hoai; Dat, Ninh Quoc; Ha, Nguyen Thi Viet (Tạp chí Nghiên cứu Y học, 2023)
Various hematological abnormalities including coagulation factor abnormalities, leukocytosis, acute hemolytic anemia, thrombocytopenia, thrombotic thrombocytopenic purpura, and disseminated intravascular coagulopathy have been reported in acute pancreatitis patients. The purpose of this descriptive cross - sectional study was to describe characteristics of coagulation disorders in 96 children with acute pancreatitis at the Vietnam National Children's Hospital. rom January 2022 to March 2023. Results showed that the mean age of children was 6.2 ± 3.2 years old, and the boy to girl ratio was 1.2 to 1, 69.8% of children had coagulation disorders. Of the 67 children who had abnormal coagulation tests, 64.2% had hypercoagulability, 35.8% had mixed hypercoagulability, 28.4% had fibrinolysis and 25.4% had disseminated intravascular coagulation. Most coagulation disorders cases showed no clinical manifestations and only 3.1% had thrombosis and hemorrhage. The factors associated with coagulopathy were hyperlipidemia and pancreatic necrosis. In conclusion, although coagulation disorders showed up in a high percentage of children with acute pancreatitis, they are difficult to be recognized based on clinical manifestations. This highlights the importance of early identification based on hemostasis testing, as it can lead to better overall management and treatment.